Stable hydrogen and carbon isotopes of C37 alkenones during Termination I and II - Sebastian Kasper; Marcel T J van der Meer; Anchelique Mets; Rainer Zahn; Jaap S Sinninghe Damsté; Stefan Schouten (PANGAEA, 2014)
At the southern tip of Africa, the Agulhas Current reflects back into the Indian Ocean causing so-called "Agulhas rings" to spin off and release relatively warm and saline water into the South Atlantic Ocean. Previous reconstructions of the dynamics of the Agulhas Current, based on paleo-sea surface temperature and sea surface salinity proxies, inferred that Agulhas leakage from the Indian Ocean to the South Atlantic was reduced during glacial stages as a consequence of shifted wind fields and a northwards migration of the subtropical front. Subsequently, this might have led to a buildup of warm saline water in the southern Indian Ocean. To investigate this latter hypothesis, we reconstructed sea surface salinity changes using alkenone dD, and paleo-sea surface temperature using TEXH 86 and UK extquotesingle37, from two sediment cores (MD02-2594, MD96-2080) located in the Agulhas leakage area during Termination I and II. Both UK extquotesingle37 and TEXH 86 temperature reconstructions indicate an abrupt warming during the glacial terminations, while a shift to more negative dDalkenone values of approximately 14 per mil during glacial Termination I and II is also observed. Approximately half of the isotopic shift can be attributed to the change in global ice volume, while the residual isotopic shift is attributed to changes in salinity, suggesting relatively high salinities at the core sites during glacials, with subsequent freshening during glacial terminations. Approximate estimations suggest that dDalkenone represents a salinity change of ca. 1.7-1.9 during Termination I and Termination II. These estimations are in good agreement with the proposed changes in salinity derived from previously reported combined planktonic Foraminifera d18O values and Mg/Ca-based temperature reconstructions. Our results confirm that the dD of alkenones is a potentially suitable tool to reconstruct salinity changes independent of planktonic Foraminifera d18O.
Supplement to: Kasper, S et al. (2014): Salinity changes in the Agulhas leakage area recorded by stable hydrogen isotopes of C37 alkenones during Termination I and II. Climate of the Past, 10(1), 251-260, https://doi.org/10.5194/cp-10-251-2014